Ober's Test and Modified Ober's Test are Reliable Means of Measuring Iliotibial Band using both Goniometer and Inclinometer - Rolandas Kesminas; Jovita Burbulevičiūtė; Saulė Sipavičienė (Lithuanian Sports University, 2019)
Research background. Iliotibial band syndrome is common among athletes due to intensive training or repetitive knee ﬂexion and extension. There is not much data about iliotibial band length on the measurement reliability in the literature. Research aim was to investigate the links and the reliability of Ober's test and Modifed Ober's test results measuring iliotibial band length using goniometer and inclinometer. Methods. Ober's test and Modifed Ober's test were performed for the estimation of iliotibial band length, and the ﬂexion angles were measured using a standard goniometer and an inclinometer. Results. Research results indicated that the values of intraclass correlation coeffcient were within the range of 0.85-0.94, so the measurement reliability (reproducibility) of Ober's test and Modifed Ober's test were estimated as good or very good. Conclusions. In Ober's test and Modifed Ober's test iliotibial band length can be reliably measured using both goniometer and inclinometer. The results of goniometric and inclinometric measurements of iliotibial band length in both Ober's test and Modifed Ober's test are reliable and their reproducibility is adequate.  Keywords: reliability, Ober's test, iliotibial band length, goniometer, inclinometer.